Cytospora tristicha (De Not.) Mlčoch comb. nov., a lesser-known pathogen of wild roses - Patrik Mlčoch; Michaela Sedlářová (Plant Protection Science)
Stem canker of Rosa pendulina, collected in south-eastern Switzerland (canton of Graubünden) in August 2022, was studied in details. The causal agent of the disease was first identified as Valseutypella tristicha (Valsaceae, Diaporthales, Ascomycota) based on microscopic characteristics. The subsequent molecular analysis classified it into the genus Cytospora and indicated that it is identical with C. rosicola, described from China in 2020 based on the molecular data, however, V. tristicha is an older name than C. rosicola, so this has priority. Thus, a new combination of the name is proposed for this fungus.